Experimental evaluation of the effectiveness of water mist automated fire extinguishing systems for oil transportation - Glushkov D. O. Dmitry Olegovich; Nyashina G. S. Galina Sergeevna; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich (Energy Efficiency and Automation Systems for Oil and Gas Facilities, 2015)
Title screen